African-American patients with cancer Talking About Clinical Trials (TACT) with oncologists during consultations: evaluating the efficacy of tailored health messages in a randomised controlled trial—the TACT study protocol. Issue 12 (16th December 2016) - Brown, R F; Davis, R; Wilson Genderson, M; Grant, S; Cadet, D; Lessard, M; Alpert, J; Ward, J; Ginder, G
Abstract : Introduction: Low rates of accrual of African-American (AA) patients with cancer to therapeutic clinical trials (CTs) represent a serious and modifiable racial disparity in healthcare that impedes the development of promising cancer therapies. Suboptimal physician–patient consultation communication is a barrier to the accrual of patients with cancer of any race, but communication difficulties are compounded with AA patients. Providing tailored health messages (THM) to AA patients and their physician about CTs has the potential to improve communication, lower barriers to accrual and ameliorate health disparities. Objective: (1) Demonstrate the efficacy of THM to increase patient activation as measured by direct observation. (2) Demonstrate the efficacy of THM to improve patient outcomes associated with barriers to AA participation. (3) Explore associations among preconsultation levels of: (A) trust in medical researchers, (B) knowledge and attitudes towards CTs, (C) patient-family member congruence in decision-making, and (D) involvement/information preferences, and group assignment. Methods and analysis: First, using established methods, we will develop THM materials. Second, the efficacy of the intervention is determined in a 2 by 2 factorial randomised controlled trial to test the effectiveness of (1) providing 357 AA patients with cancer with THM with 2 different 'depths' of tailoring and (2) either providing feedback to oncologists about the patients' trial THM or not. The primary analysis compares patient engaged communication in 4 groups preconsultation and postconsultation. Ethics and dissemination: This study was approved by the Virginia Commonwealth University Institutional Review Board. To facilitate use of the THM intervention in diverse settings, we will convene 'user groups' at 3 major US cancer centres. To facilitate dissemination, we will post all materials and the implementation guide in publicly available locations. Trial registration number: NCT02356549.